The association of bone and osteoclasts with vascular calcification. (December 2015) - Han, Kum Hyun; Hennigar, Randolph A; O'Neill, W Charles
The presence of bone tissue in calcified arteries may provide insights into the pathophysiology and potential reversibility of calcification, but the prevalence, distribution, and determinants of bone and osteoclasts in calcified arteries are unknown. Specimens of 386 arteries from lower limb amputations in 108 patients were examined retrospectively. Calcification was present in 282 arteries from 89 patients, which was medial in 64%, intimal in 9%, and both in 27%. Bone was present in 6% of arteries, essentially all of which were heavily calcified. Multiple sampling revealed that the true prevalence of bone in heavily calcified arteries was 25%. Bone was more common in medial rather than intimal calcifications (10% vs 3%, p =0.03) but did not vary with artery location (above vs below the knee). Heavily calcified arteries with bone were more likely to come from patients who were older ( p =0.04), had diabetes ( p =0.06), or were receiving warfarin ( p =0.06), but there was no association with gender or renal failure. Bone was almost always adjacent to calcifications, along the periphery, but never within. Staining for the bone-specific proteins osteocalcin and osterix was noted in 20% and 45% of heavily calcified arteries without visible bone. Osteoclasts were present in 4.9% of arteries, all of which were heavily calcified and most of which contained bone. The frequent absence of bone in heavily calcified vessels and the histologic pattern strongly suggests a secondary rather than primary event. Recruitment of osteoclasts to vascular calcifications can occur but is rare, suggesting a limited capacity to reverse calcifications.